World War I - Williams, Brian, 1943- (New York, N.Y. : DK Pub., 2018)
Presents facts, figures, and pictures of World War I, featuring the war's critical moments, key players, and lasting effects paired with a timeline, maps, and more.
Includes index.
Map on endpapers.
5.0
3-6.
3-6
Keywords: World War, 1914-1918 -- Juvenile literature; World War, 1914-1918.; World War, 1914-1918.